PROFILE OF CHARACTERISTIC, RISK FACTOR, AND CLINICAL SEVERITY OF ISCHEMIC STROKE PATIENTS - Perdana, Philips Carel; Ardhi, Mohammad Saiful; Susanto, Hermawan (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2024)
Background: Ischemic strokes account for 87% of all strokes, making them the second leading cause of disability and one of the leading causes of mortality worldwide. Using the National Institutes of Health Stroke Scale (NIHSS), the clinical severity of an ischemic stroke can be assessed. Objective: The objective of this study is to ascertain the clinical severity, risk factors, and characteristics of patients with ischemic stroke at the neurology department of RSUD Dr. Soetomo Surabaya. Methods: The participants in this descriptive observational study comprise individuals who sought medical attention at the neurology department of RSUD Dr. Soetomo between January 2019 and December 2020 due to an ischemic stroke. The observed profile comprises the following factors: age, gender, obesity, smoking status, alcohol consumption, physical inactivity, family history of vascular disease, form of infarction, dyslipidemia, hypertension, cholesterol, and diabetes. Results: In the medical record data collection of 89 ischemic stroke patients, 36 patients were excluded when they first entered the hospital. So a total of 53 ischemic stroke patients were collected. 29 (54.72%) patients are male. The age range is dominated by 48 - 62 years from 29 (54.72%) patients. 44 (83.02%) patients are Javanese. 18 (33.96%) patients had a history of smoking, 1 (1.89%) patient consumed alcohol, and 1 (1.89%) patients were inactive physically. 13 (24.53%) patients have a family history of vascular disease, 45 (84.91%) patients have hypertension, 26 (49.06%) patients have dyslipidemia, and 19 (35.85%) patients have diabetes. 34 (64.15%) patients had moderate strokes, 15 (28.30%) patients had mild strokes, 2 (3.77%) patients had moderate-severe strokes, and 2 (3.77%) patients had severe strokes according to the results of the NIHSS assessment on the first admission. Conclusion: Ischemic stroke patients were mostly in the age range of 48 – 62 years. Comorbidities such as hypertension, dyslipidemia, hypertriglyceridemia, and diabetes are present in the majority of patients. The NIHSS scoring identified moderate stroke patients as having the most frequent outcomes, followed by patients with mild stroke.